Jewish Wit - In the Original, and in Translation - Hessing, Jakob (Naharaim, 2024)
This essay, based on Prof. Hessing's keynote lecture delivered at the opening of the Gronemann-conference in 2022, explores notions of "Jewish wit" in Sammy Gronemann's German novel Tohuwabohu (translated as Utter Chaos). It focuses on the incongruities and comic potential of the tensions between German and Yiddish in the novel, questioning notions of "original" and "translation" as applied to the interrelationships between Eastern European and German Jewish cultures. By highlighting the linguistic and cultural shifts experienced by these Jewish communities, Gronemann's novel serves as a focal point for dissecting the nuances of multilingual Jewish humor and the underlying tragedies of Jewish life, especially amidst historical upheavals like World War I and the Holocaust. The essay concludes with insights into Gronemann's ironic perspective on Zionism and the thematic significance of "Tohuwabohu" as a metaphor for the modern Jewish experience.